Free School Meal, Islamic Education, and Human Capital Development Among Indonesian Muslim Generation - Fahrul Radhi; M. Ikhwan; Siti Aminah; M. Agus Wahyudi (Jurnal Eduslamic, 2026)
The quality of the Muslim generation in Indonesia remains a pressing concern, particularly due to persistent issues such as malnutrition and stunting, which adversely affect cognitive development, educational achievement, and long-term human capital. In response, the Free School Meal (Makan Bergizi Gratis/MBG) has been introduced as a strategic policy to improve children's nutritional status and support learning outcomes. This study examines the MBG program through the lens of Islamic education and explores its contribution to enhancing the quality of the Muslim generation. Employing a qualitative, normative, and library-based research design, data were drawn from policy documents, academic literature, and relevant sources, and analyzed using content analysis. The findings indicate that adequate nutrition significantly enhances cognitive function, physical health, and academic performance. From an Islamic educational perspective, the notion of a high-quality generation aligns with the concept of insan kamil, emphasizing holistic development across spiritual, intellectual, moral, and physical dimensions. The MBG program reflects key Islamic values, including halal and tayyib, social responsibility, and public welfare (maslahah ‘ammah). Its effectiveness, however, depends on sustained implementation and integration with educational frameworks.